Practical considerations on Quantum Key Distribution (QKD) - Al-Khateeb, Wajdi Fawzi Mohammed; Al-Khateeb, Khalid A. Saeed; Ahmad, Nur Elyana; Mohd Salleh, Siti Norussaadah (The Institute of Electrical and Electronics Engineers, Inc., 2013)
The advancement of the quantum computing is challenging the foundation of the cryptography by its almost unlimited computation power to predict the secure key that is thought to be absolutely secure based on the currently used algorithms such as the RSA and the Diffie-Hellman and others. The field of quantum cryptography on the other hand is providing the needed highly secure keys through the introduction of quantum key distribution QKD when the quantum computing becomes a reality. However, the quantum cryptography and the QKD are challenged in many ways, not only to provide the advanced level of technology but also to overcome many constraints to provide a worldwide practical distribution system as well as to provide the efficiency to overcome the very modest size of the quantum keys. In this paper, practical factors affecting realistic QKD are investigated supported by related simulation based analysis.